The Effect of Patient Migration in Bed on Torso Elevation. Issue 3 (May 2015) - Wiggermann, Neal; Kotowski, Susan; Davis, Kermit; VanGilder, Catherine
Abstract : Background: Elevating the hospital head of bed (HOB) to at least 30° is recommended practice to reduce the risk of ventilator-associated pneumonia (VAP) in mechanically ventilated patients. However, this common practice prescribes the position of the bed and not of the patient, which could be significantly different. Objective: The aim of this research was to determine the relationship between patient migration in bed and anatomic torso angle. Methods: Ten healthy participants were positioned in a hospital bed that was raised from flat to 30° and 45° HOB elevations. Prior to bed movement, participants were aligned to different locations along the length of the bed to represent different amounts of migration. A motion capture system was used to measure torso angle and migration toward the foot of the bed. The relationship between torso angle and migration was estimated by linear regression. Results: Patient migration resulted in lower torso angles for both 30° and 45° HOB articulations. A migration of 10 cm resulted in a loss of 9.1° and 13.0° of torso angle for HOB articulations of 30° and 45°, respectively (for 30° articulations: β = −0.91, R 2 = .96; for 45° articulations: β = −1.30, R 2 = .98). Discussion: Migration toward the foot of the bed flattens the torso. To maintain a torso angle that is likely to protect against VAP, healthcare providers need to manage both HOB angle and migration. Protocols and equipment that minimize patient migration will help support effective clinical practice. Future research on patient migration, as it relates to VAP or other outcomes, should measure patient torso angle to allow accurate translation of the results to care practice.